Chemical reaction impacts on squeezing radiative flow of sodium alginate-based casson ternary nanofluid with magnetohydrodynamics - N.A.A. Jalil; S. Shafie; N.A.M. Noor (Alexandria Engineering Journal)
This research investigates the dynamic magnetohydrodynamics flow and radiative heat transfer of Casson Ternary Nanofluid (TN) flowing between two parallel surfaces within a porous medium accompanied by chemical reactions. The TN comprises of Graphene, Graphene Oxide, and Silver dispersed in Sodium Alginate. The governing equations are transformed into dimensionless equations using appropriate similarity variables and solved by Keller-box method. The study discusses the effects of squeeze, magnetic fields, porous medium, chemical reactions, nanoparticles volumetric percentage, and thermal radiation on flow behavior and physical quantities. Comparison of the obtained results with previously published outcomes demonstrates satisfactory agreement, validating the method. The results reveal that squeezing between the parallel surfaces enhances fluid velocity, with a slowdown observed in the center as parameters Hartmann number as well as volume fractions of nanoparticles increase. Convective heat transfer and temperature decrease with rising values of chemical reaction along with volume fractions of nanoparticles. Concentration increases and mass transfer rate decreases with constructive chemical reactions, while opposite trends are observed for destructive chemical reactions.